Análisis del principio de pertinencia de la carrera de Administración Pública en el período 2017-2019 - Carreño Anzules, Edison Javier (2021)
This work was developed with the purpose of analyzing the principle of relevance of the Public Administration career in the period 2017-2019. The quantitative and qualitative analysis was used as a methodology, through the application of a survey, information was collected from the graduates who were working. The directors of the Human Talent departments of the public institutions corresponding to the cantons of Bolívar, Chone, Rocafuerte, Portoviejo and Montecristi were also interviewed; this technique was intended to collect qualitative data, which allowed to know the degree of relevance of the career, and identify critical nodes. The results showed that there is a low level of employability of graduates due to certain requirements demanded by employers such as work experience and knowledge in specific areas related to methodologies, mathematics and statistics. It is concluded that the curricular mesh with contents should be improved and strengthened according to the new labor demands, therefore actions were proposed to strengthen the level of relevance, in this way increasing the labor insertion in institutions within the public sector for graduate professionals in the career of Public Administration at the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López.